A polymer‐based systemic hemostat for managing uncontrolled bleeding - Yongsheng Gao; Mayumi Ikeda‐Imafuku; Zongmin Zhao; Maithili Joshi; Samir Mitragotri (Wiley, 2023)
Abstract Uncontrolled bleeding is a life‐threatening emergency that requires immediate intervention. Currently available on‐site bleeding interventions largely rely on the use of tourniquets, pressure dressing, and other topical hemostatic agents, which can only treat bleeding injuries that are known, accessible, and potentially compressible. Synthetic hemostats that are stable at room temperature, easy to carry, field‐usable, and able to stop internal bleeding at multiple or unknown sources, are still lacking. We recently developed a hemostatic agent via polymer peptide interfusion (HAPPI), which can selectively bind to activated platelets and injury sites after intravascular administration. Here we report that HAPPI is highly effective in treating multiple lethal traumatic bleeding conditions in normal as well as hemophilia models via either systemic administration or topical application. In a rat liver traumatic model, intravenous injection of HAPPI resulted in a significant decrease in blood loss and a four‐fold reduction in mortality rate within 2 h after injury. When applied topically on liver punch biopsy wounds in heparinized rats, HAPPI achieved a 73% of reduction in blood loss and a five‐fold increase in survival rate. HAPPI also exhibited hemostatic efficacy in hemophilia A mice by reducing blood loss. Further, HAPPI worked synergistically with rFVIIa to induce immediate hemostasis and 95% reduction in total blood loss compared to the saline‐treated group in hemophelia mice models. These results demonstrate that HAPPI is a promising field‐usable hemostatic agent for a broad range of different hemorrhagic conditions.